EFFICACY OF BACILLUS THURINGIENSIS BERLINER SUBSPECIES KURSTAKI AND AIZAWAI AGAINST THE BAGWORM, METISA PLANA WALKER ON OIL PALM - Tan Sek Yee; Yusof Ibrahim; Dzolkhifli Omar (Tropical Life Sciences Research, 2008)
The efficacy of Bacillus thuringiensis subspecies kurstaki (Btk) and aizawai (Bta) against the third and fifth instar larvae of Metisa plana on oil palm was studied. The objective of the study was to determine the level of kill achievable with six selected Bt products on M. plana. Laboratory bioassays were performed on formulations containing Btk: Dipel® ES, Dipel® DF, Dipel® WP and ABG-6429 FC® (research formulation), and Bta: Florbac® SC and Xentari® WG at temperatures of 24°C–29°C and 55%–80% relative humidity (RH) by using leaf dipping method. Both subspecies were shown to be effective on the bagworms. In most cases, the third instar larvae required lesser amount of Bt and shorter time for a satisfactory kill compared to the fifth instar larvae. Efikasi Bacillus thuringiensis subspesies kurstaki (Btk) dan aizawai (Bta) terhadap larva instar ketiga dan kelima Metisa plana pada kelapa sawit telah dikaji. Tujuan kajian ialah untuk menentukan tahap kematian yang boleh dicapai oleh enam produk Bt terpilih terhadap M. plana. Bioasai di makmal telah dijalankan ke atas formulasi yang mengandungi Btk: Dipel® ES, Dipel® DF, Dipel® WP dan ABG-6429 FC® (formulasi untuk penyelidikan), dan Bta: Florbac® SC dan Xentari® WG pada suhu 24°C–29°C dan 55%–80% kelembapan bandingan (RH) dengan menggunakan kaedah celupan daun. Kedua-dua subspecies telah menunjukkan keberkesanannya terhadap ulat bungkus itu. Dalam kebanyakan keadaan, larva instar ketiga memerlukan sedikit Bt serta masa yang singkat untuk mengakibatkan kematian berbanding larva instar kelima.